THE ROLE OF ONLINE APPS AND SITES IN LEARNING FOREIGN LANGUAGES - Zokirjonova Maftuna Zokirjon kizi; Khudoynazarova Dildora Shonazar kizi (Western European Studies, 2024)
This article explores the widespread use of learning tools among language learners, particularly focusing on technology-driven learning approaches. It delves into how modern technologies, such as mobile apps and online platforms, have transformed language acquisition methods, emphasizing their prevalence and effectiveness in today's educational landscape.
Keywords: Duolingo; apps; advantages; disadvantages of online learning